Evaluación económica de la producción de huevo fértil. Caso de estudio en Costa Rica - Solórzano Thompson, Johanna (2024)
The consumption of chicken meat and chicken eggs has increased in the last decade and has become an essential element of the Costa Rican diet. In this way, the market is led by a few companies which are integrated in different ways to reach the consumer’s table. Due to its importance, the aim of this study was carried out an economic evaluation of the production of fertile eggs using heavy breeders of Cobb breed by a case study where was analyzed the requirements of a production of more than 30 thousand farmer birds by 2031. The results were demonstrated that technical and economic viability was positive for an evaluation horizon of 10 years.